2017
DOI: 10.1638/2016-0025r1.1
|View full text |Cite
|
Sign up to set email alerts
|

FIRST RECORD OF HEMATOLOGIC VALUES IN FREE-LIVING AND CAPTIVE MANED SLOTHS (BRADYPUS TORQUATUS; XENARTHA, BRADYPODIDAE)

Abstract: Bradypus torquatus is a rare and endemic sloth species from the Atlantic Forest, Brazil. Due to a lack of medical information including hematologic reference parameters for the species, hematologic baseline values were determined using samples from 14 clinically healthy B. torquatus , under captive (n = 7) and free-living (n = 7) conditions in Bahia State, Brazil. Additionally, the morphology of the blood cells is presented, with a demonstration that the Barr body chromosome may assist with sex determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, this practice needs to be applied with caution as the values can often vary from species to species. Catenacci et al 17 reported RIs for the maned sloth, Bradypus torquatus , an endemic species in some regions of the Atlantic rainforest. Comparing their results with ours, one can notice that some variables share similar values, including those for RBC, hemoglobin, PCVs, WBCs, and relative segmented neutrophil and monocyte values.…”
Section: Discussionmentioning
confidence: 99%
“…However, this practice needs to be applied with caution as the values can often vary from species to species. Catenacci et al 17 reported RIs for the maned sloth, Bradypus torquatus , an endemic species in some regions of the Atlantic rainforest. Comparing their results with ours, one can notice that some variables share similar values, including those for RBC, hemoglobin, PCVs, WBCs, and relative segmented neutrophil and monocyte values.…”
Section: Discussionmentioning
confidence: 99%